2000
DOI: 10.1080/003655200750024191
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colorectal Tumor and Inflammatory Bowel Disease during Follow-up of Patients with Initial Diagnosis of Irritable Bowel Syndrome

Abstract: IBS and FD shared some comorbidity features, yet demographics and incidence rates were different. Unlike the detection of colorectal tumor, the excess risk of IBD after an initial diagnosis of IBS was cumulatively increased during all the follow-up period. The continuously increased risk of IBD detection in IBS patients favors a true association between IBS and IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 8 publications
8
45
1
1
Order By: Relevance
“…During this period they also saw initially high rates of IBD and CRC fall in the first year. They reported a crude incidence of 26.2 CRCs diagnosed per 10000 patient years [12], (considerably higher than we report over the complete follow-up now available, but similar to the incidence we found in the early follow-up period), and no overall excess compared to controls. They found an overall crude incidence of IBD of 17.8 cases per 10000 person years, 16 times the rate in controls [12] which is similar to our finding.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…During this period they also saw initially high rates of IBD and CRC fall in the first year. They reported a crude incidence of 26.2 CRCs diagnosed per 10000 patient years [12], (considerably higher than we report over the complete follow-up now available, but similar to the incidence we found in the early follow-up period), and no overall excess compared to controls. They found an overall crude incidence of IBD of 17.8 cases per 10000 person years, 16 times the rate in controls [12] which is similar to our finding.…”
Section: Discussionsupporting
confidence: 84%
“…Shorter studies are likely to be biased by the higher rates we have shown in the first 12 months, probably related to the diagnostic work-up for IBS. Our study adds 12 years of follow-up to the findings of Garcia-Rodriguez et al [12], allowing assessment of how incidence of organic disease changes over time since IBS diagnosis. Since most IBS diagnoses are made among those under 50 years such prolonged follow up is of particular importance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The correlation between intestinal infection and IBS was well documented [2]. Through a cohort study, Rodríguez found that, after an episode of gastroenteritis, patients were ten times more likely to have IBS than were subjects in the general population [3]. Although the pathophysiology of post-infection irritable bowel syndrome (PI-IBS) is heterogeneous and not fully elucidated, some results have suggested that there are abnormalities of motility [4] and visceral sensitivity [5] in patients with PI-IBS.…”
Section: Introductionmentioning
confidence: 97%